An assessment of metals (Pb and Cu) contamination in bottom sediment from South China sea coastal waters, Malaysia - Ong, Meng Chuan; Yunus, Kamaruzzaman (Science Publications, 2009)
Problem statement: The accumulation of metal contaminants in sediments can pose serious environmental problems to the surrounding areas. Trace metal contamination in sediment could affect the water quality and the bio-assimilation and bioaccumulation of metals in aquatic organisms, resulting in potential long-term implications on human health and ecosystem. Approach: About 154 bottom sediment samples were collected using Smith McIntyre in a transect pattern from South China Sea East Coast coastal water (Terengganu, Pahang and Johor coastal area). The study focused on the levels of Pb and Cu in order to assess the extent of environment pollution and to discuss the origin of these contaminants in the sediment. Results: Results showed that the average concentration of Pb and Cu was 33.70 μg g-1 dry weights and 22.40 μg g-1 dry weights, respectively. Pb and Cu have relatively lower Enrichment Factors (EF) value and geo-accumulation (Igeo) indices in study area and these analysis validated that elevated heavy metals concentration in most sample are not due to artificial contamination. Conclusion: Overall, geochemistry of the samples showed the effect of both natural and anthropogenic inputs to the catchment, however, natural processes were more dominant than anthropogenic inputs in concentrating metals. Results obtained would help to develop strategies for pollution control and sediment remediation of coastal waters in the South China Sea. © 2009 Science Publications.